ECOMMERCE SERVICES AS A PART OF POSTAL ELECTRONIC SERVICES - Nemcek, Bystrik (Doprava a spoje, 2012)
The article is dedicated to the development of product and services related to the gradual electronisation in postal sector. There is defined the general dividing of postal electronic services. The contribution contains also clasification and characterization of services that belong to the area of eCommerce. Also there is realized analyse of postal electronic services providing in selected countries for eCommerce. It also includes information about number of postal e-services introduced globally each year.